Evaluating active transport benefits and costs. Guide to valuing walking and cycling improvements and encouragement programs. - Litman, Todd (My University, 2013)
The report describes methods for evaluating non-motorized transport (walking, cycling, and their variants) benefits and costs, including direct benefits to users from improved walking and cycling conditions, and various benefits to society from increased nonmotorized travel activity, reduced automobile travel, and support for more compact land use development. It identifies various types of benefits and costs, and describes methods for measuring them. It discusses non-motorized transport demand and ways to increase non-motorized travel activity. This analysis indicates that non-motorized travel provides significant benefits, many of which are overlooked or undervalued in conventional transport economic evaluation.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Kosten-Nutzen-Analyse; Wirkungsanalyse; Radverkehrsförderung; Studie; Nichtmotorisierter Verkehr